Legal Protection of Industrial Property Rights - Messaour, Djalila (Journal of Legal Studies and Researches, 2024)
The aim of this topic is to determine the industrial property rights provided by the Algerian legislator, searching for means of protection that garantee the use of these right exclusively by their holders, and prevent their exploitation by others in illegal ways. The legislator has introduced legal and judicial reforms, especially by organizing the reconciliation procedure and establishing commercial courts for the resolution of disputes arising from it.